Interaction of insecticidal proteins from Pseudomonas spp. and Bacillus thuringiensis for boll weevil management - Rodrigues, Jardel Diego Barbosa [UNESP]; Moreira, Raquel Oliveira [UNESP]; de Souza, Jackson Antônio Marcondes [UNESP]; Desidério, Janete Apparecida [UNESP] (Public Library of Science (PLoS), 2023)
Cotton crop yields are largely affected by infestations of Anthonomus grandis, which is its main pest. Although Bacillus thuringiensis (Bt) derived proteins can limit insect pest infestations, the diverse use of control methods becomes a viable alternative in order to prolong the use of technology in the field. One of the alternative methods to Bt technology has been the utilization of certain Pseudomonas species highly efficient in controlling coleopteran insects have been used to produce highly toxic insecticidal proteins. This study aimed to evaluate the toxicity of IPD072Aa and PIP-47Aa proteins, isolated from Pseudomonas spp., in interaction with Cry1Ia10, Cry3Aa, and Cry8B proteins isolated from B. thuringiensis, to control A. grandis in cotton crops. The genes IPD072Aa and PIP-47Aa were synthesized and cloned into a pET-SUMO expression vector. Moreover, Cry1Ia10, Cry3Aa, and Cry8B proteins were obtained by inducing recombinant E. coli clones, which were previously acquired by our research group from the Laboratory of Bacteria Genetics and Applied Biotechnology (LGBBA). These proteins were visualized in SDS-PAGE, quantified, and incorporated into an artificial diet to estimate their lethal concentrations (LC) through individual or combined bioassays. The results of individual toxicity revealed that IPD072Aa, PIP-47Aa, Cry1Ia10, Cry3Aa, and Cry8B were efficient in controlling A. grandis, with the latter being the most toxic. Regarding interaction assays, a high synergistic interaction was observed between Cry1Ia10 and Cry3Aa. All interactions involving Cry3Aa and PIP-47Aa, when combined with other proteins, showed a clear synergistic effect. Our findings highlighted that the tested proteins in combination, for the most part, increase toxicity against A. grandis neonate larvae, suggesting possible constructions for pyramiding cotton plants to the manage and the control boll weevils.